Silenciamento gênico por interferência de RNA (RNAi) de transcritos de Schistosoma mansoni - Marina de Moraes Mourao (2009)
RNA interference (RNAi) represents the only reverse genetic method currently available for manipulating gene-specific expression in Schistosoma spp., since knockout and super-expression induction are not feasible in this parasite. Lately, RNAi has been widely used for gene silencing, but its application as a functional genomic profiling tool in helmints has yet to be explored. In the present study 33 genes, including transcription factors, cell signaling molecules, metabolic enzymes and antioxidants, were selected to determine if gene knockdown by RNAi was associated with morphologically definable phenotypic changes in early intramolluscan larval development. Transcript selection was based on their high expression in in vitro cultured S. mansoni primary sporocysts and/or their potential involvement in developmental processes, such as the anti-oxidants enzymes which are produced by the parasite Schistosoma mansoni and are believed to be involved in the maintenance of cellular redox balance, thus contributing to larval survival in their intermediate snail host, Biomphalaria glabrata. At the present study, miracidia were allowed to transform to sporocysts in the presence of synthesized double-stranded RNAs (dsRNAs) and cultivated for 7 days, during which time developing larvae were closely observed for phenotypic changes including failure/delay in transformation, loss of motility, altered growth and death. Of the phenotypes evaluated, only one was consistently detected; namely a reduction in sporocyst size based on length measurements. The size-reducing phenotype was observed in 11 of the 34 dsRNA treatment groups, and of these, 11 phenotype-associated genes (SOD, Smad1, RHO2, Smad2, Cav2A, ring box, GST26, calcineurin B, Smad4, lactate dehydrogenase and EF1). Após sete dias de incubação com dsRNA, apenas 6 tratamentos demonstraram consistente e significante diminuição nos níveis de transcritos medidos por qRT-PCR. After seven days of incubation, only 6 treatments demonstrated a significant and consistent knockdown of specific transcript expression was detected by q-PCR. Unexpectedly one phenotype-linked gene, SOD, was highly induced (~1600-fold) upon dsRNA exposure. Variation in dsRNA-mediated silencing effects also was evident in the group of sporocysts that lacked any definable phenotype. Out of 23 nonphenotype-expressing dsRNA treatments, 14 were assessed for the transcript levels. Of those, 7 genes exhibited consistent reductions in steady-state transcript levels, while expression level for the rest remained unchanged. Results demonstrate that the efficacy of dsRNA-treatment in producing phenotypic changes and/or altered gene expression levels in S. mansoni sporocysts is highly dependent on the selected gene (or the specific dsRNA sequence used) and the timing after treatment. Aditionally, we have focused on the functional characterization of specific anti-oxidant enzymes, including GST26, GST28, GPx, TPx1/2 and SOD, known to be involved in cellular redox reactions, in an attempt to evaluate their endogenous anti-oxidant function in the early-developing primary sporocyst stage of S. mansoni. Further, we show that treatment of sporocysts with dsRNA of EF1, GST26 or TPx1/2, resulted in a significant decrease (80%, 90% and 50%, respectively) using Western blot analysis compared to dsRNA-GFP control treatment. These results were further confirmed by immunocytochemistry. Experiments were then conducted to determine if anti-oxidant RNAi-induced protein knockdown had a modulating effect on in vitro parasite survival in presence of a sublethal concentration of H2O2. Results clearly demonstrated a significantly higher susceptibility of GST26, GST28, TPx1/2 and GPx dsRNA-treated larvae to H2O2 oxidative stress (60-80% mortalities at 48 hr) compared to GFP dsRNA controls (~15 % mortality). Co-culture of hemocytes and sporocyts allowed evaluating the hypothesis that reducing the antioxidant ability of sporocysts during hemocyte encapsulation reactions would increase their vulnerability to sublethal levels of ROS normally produced by susceptible snail hemocytes. Hence, we demonstrate that GST26, GST28 and TPx1/2-modified sporocysts survival was affected after 24 hours of co-culture, showing the significant protective role of TPxs and GSTs in sporocysts during susceptible intermediate host B. glabrata interaction Although RNAi holds great promise as a functional genomics tool for larval schistosomes, our finding of variable efficiencies in specific gene knockdown indicate a critical need for gene-specific testing and optimization as an essential part of experimental design, execution, and data interpretation. Moreover, anti-oxidant functional experiments strongly support the hypothesis that endogenous expression and regulation of larval anti-oxidant enzymes serve a direct role in protection against external oxidative stress, including immune-mediated cytotoxic reactions.